2001
DOI: 10.1016/s0002-9440(10)64002-3
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Interaction with Inflamed Postcapillary Venule Endothelium Alters Annexin 1 Expression

Abstract: Annexin 1 (ANX-A1) exerts antimigratory actions in several models of acute and chronic inflammation. This is related to its ability to mimic the effect of endogenous ANX-A1 that is externalized on neutrophil adhesion to the postcapillary endothelium. In the present study we monitored ANX-A1 expression and localization in intravascular and emigrated neutrophils, using a classical model of rat peritonitis. For this purpose, a pair of antibodies raised against the ANX-A1 N-terminus (ie, able to recognize intact A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
108
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 64 publications
9
108
0
Order By: Relevance
“…For instance, experimental evidence in animal models as well as in humans indicated marked presence of ANXA1 in inflammatory exudates (Ambrose et al 1990b, Smith et al 1990, Vergnolle et al 1995, suggesting a physiological role for ANXA1 in modulating neutrophil survival at sites of inflammation. In situ hybridization analysis showed de novo ANXA1 synthesis in extravasated neutrophils (Oliani et al 2001a) supporting the concept of feedback control on neutrophil activity. Clearly, any effect favouring neutrophil apoptosis or removal of apoptotic cells promotes mechanisms of anti-inflammation and activates pathways crucial to control the host inflammatory response (Ward et al 1999).…”
Section: Anxa 1 Actions On Polymorphonuclear Leukocytesmentioning
confidence: 59%
See 1 more Smart Citation
“…For instance, experimental evidence in animal models as well as in humans indicated marked presence of ANXA1 in inflammatory exudates (Ambrose et al 1990b, Smith et al 1990, Vergnolle et al 1995, suggesting a physiological role for ANXA1 in modulating neutrophil survival at sites of inflammation. In situ hybridization analysis showed de novo ANXA1 synthesis in extravasated neutrophils (Oliani et al 2001a) supporting the concept of feedback control on neutrophil activity. Clearly, any effect favouring neutrophil apoptosis or removal of apoptotic cells promotes mechanisms of anti-inflammation and activates pathways crucial to control the host inflammatory response (Ward et al 1999).…”
Section: Anxa 1 Actions On Polymorphonuclear Leukocytesmentioning
confidence: 59%
“…The protein does not seem to be mobilized during the short time frame (15-30 min) of the neutrophil adhesion assays (Perretti et al 1996b), however it is possible that changes may be evident over longer periods. For instance, in an in vivo model of inflammation, endothelial ANXA1 levels increase following neutrophil diapedesis as observed 4 hours post-carrageenin injection (Oliani et al 2001a). Even less has been done in terms of endothelial cell functions.…”
Section: Anxa 1 Actions On Other Cellsmentioning
confidence: 99%
“…In fact, annexin 1 added to activated human granulocytes is quickly cleaved within its N-terminal domain, most likely by a liberated granulocyte protease (U. Rescher and A. Wilbers, unpublished observation). A substantial degree of N-terminal annexin 1 proteolysis also occurs within cells, e.g., in neutrophils upon extravasation into the subendothelium (29). Collectively, these data indicate that the N-terminal annexin 1 peptide is the physiologically active entity released from cells or generated extracellularly at sites of inflammation.…”
Section: Discussionmentioning
confidence: 76%
“…27, 9, 23). Moreover, proteolytic cleavage at position 26 of the N-terminal domain was previously shown to occur in different cells and N-terminal proteolysis was markedly induced upon neutrophil extravasation with only 25% of neutrophil annexin 1 remaining intact (28,29). Because this strongly suggested that the N-terminal peptide Ac1-25 is the physiological and pathophysiological active compound, Ac1-25 was used throughout the study.…”
Section: Annexin 1 Peptide-induced Activation Of Human Leukocytesmentioning
confidence: 99%
“…Inhibitory anti-JAM-A antibody (J10.4) was generated as previously described (34). Recombinant AnxA1 and Ac2-26 (Ac-AMVSEFLKQAWFIENEEQEYVQTVK) were generated as previously described (35)(36)(37). Scramble control peptide (Ac-YES-QFKAVWVEINTQQMLKFEAEEV) was obtained through the Emory Microchemical Facility (Emory University, Atlanta, GA), WKYMVm (m is D isomer) from Global Peptide (Fort Collins, CO), and fMLP from Sigma.…”
Section: Methodsmentioning
confidence: 99%